Group coaching as a technology of the whole student’s personality forming - Andrij Gulenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article describes: the psychological features of formation of the whole person in a modern multicultural society; the results of literature analysis; special attention is paid on the achievements of cultural-historical approach, schools of positive psychology and existential psychology. The Authors methodology of empirical research is given. The analysis of various forms of material in collection of empirical research. The criteria and types of personal integrity, depending on the dominance in humans of certain social principals are characterized. The results of quantitative and qualitative analyzes of subjective well-being, basic life existences, features of the time-orientation and self-realization of research participants as an indicator of their personal integrity are presented.